THE ROLE OF ANAK JALANAN AT-TAMUR ISLAMIC BOARDING SCHOOL IN INTERNALIZING THE VALUES OF RELIGIOUS MODERATION TO COLLEGE STUDENTS IN BANDUNG - Yusuf, Muhamad; Alwis, Alwis; Putra, Eka; Witro, Doli; Nurjaman, Andri (Islam Futura, 2023)
The emergence of the concept of religious moderation initiated by the Ministry of Religion of the Republic of Indonesia and set forth in the 2020-2024 National Medium-Term Development Plan (RPJMN) indicates that the program for internalizing and strengthening the values of religious moderation is very important and urgent to implement. The values of religious moderation consist of four points, namely national commitment, tolerance, anti-radicalism, and accommodative to local culture. The direction to internalize the four values of religious moderation is also played by the Anak Jalanan At-Tamur Islamic Boarding School, Bandung. This article aims to reveal the role of the Anak Jalanan At-Tamur Islamic Boarding School in internalizing the values of religious moderation to students. This article uses qualitative research methods that are field research. The research data were obtained from two sources, namely field data sources and library data sources. Data collection techniques used are observation, interviews, and documentaries. The data analysis techniques used are data condensation, data presentation, and drawing conclusions. The results showed that success in internalizing the values of religious moderation to students could be seen from the indicators or values of religious moderation. The four indicators (values) of religious moderation are reflected in the routine activities and attitudes of students of the Anak Jalanan At-Tamur Islamic Boarding School. Commitment to nationalism, tolerance, anti-radicalism and accommodativeness to local culture is imprinted in the personalities of the students of the Anak Jalanan At-Tamur Islamic Boarding School. This is also due to two things: firstly, interfaith dialogue events are often held and secondly, the leader of the Anak Jalanan At-Tamur Islamic Boarding School who has a broad and open view and emphasizes morality in his education.